The impact on dietary outcomes of licensed and brand equity characters in marketing unhealthy foods to children: A systematic review and meta‐analysis. (9th March 2022) - Packer, Jessica; Russell, Simon J.; McLaren, Katie; Siovolgyi, Gabriela; Stansfield, Claire; Viner, Russell M.; Croker, Helen
Summary: Licensed and brand equity characters are used to target children in the marketing of products high in fat, salt, and sugar (HFSS), but the impact of characters on dietary outcomes is unclear. The primary aim of this review was to quantify the impact of both licensed and brand equity characters on children's dietary outcomes given that existing regulations often differentiates between these character types. We systematically searched eight interdisciplinary databases and included studies from 2009 onwards until August 2021, including all countries and languages. Participants were children under 16 years, exposure was marketing for HFSS product with a character, and the outcomes were dietary consumption, preference, or purchasing behaviors of HFSS products. Data allowed for meta‐analysis of taste preferences. A total of 16 articles (including 20 studies) met the inclusion criteria, of which five were included in the meta‐analysis. Under experimental conditions, the use of characters on HFSS packaging compared with HFSS packaging with no character was found to result in significantly higher taste preference for HFSS products (standardized mean difference on a 5‐point scale 0.273; p  < 0.001). Narrative findings supported this, with studies reporting impact of both character types on product preferences including food liking and snack choice. There was limited evidence on the impact on purchase behaviors and consumption. These findings are supportive of policies that limit the exposure of HFSS food marketing using characters to children.